Epidemiology of Communicable and Non-Communicable Diseases - Attributes of Lifestyle and Nature on Humankind 2016
DOI: 10.5772/64306
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Survival to Discharge of Newborns in a Middle-Income Country

Abstract: Clinical and mortality audit is an essential part of quality improvement in health care; information obtained in this process is used to develop targeted interventions to improve outcome. This study aimed to determine predictors of short-term survival in neonates. An existing neonatal database was reviewed. A total of 5018 neonates > 400 g admitted to a tertiary hospital (Johannesburg South Africa) between 1 January 2013 and 31 December 2015 were analysed. Mean birth weight was 2148 g (standard deviation [SD]:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The current study showed that neonates who had very low birth weight had 83% delayed to recovery from RD and that of low birth weight had 50% risk of delayed compared to normal birth weights. These findings are supported by a study performed in South Africa [ 24 ] and Uganda [ 25 ].The proportion surviving increases as birth weight increases, which means that neonates with low birth weights stayed in hospitals for a longer period of time than those with normal birth weights.…”
Section: Discussionsupporting
confidence: 83%
“…The current study showed that neonates who had very low birth weight had 83% delayed to recovery from RD and that of low birth weight had 50% risk of delayed compared to normal birth weights. These findings are supported by a study performed in South Africa [ 24 ] and Uganda [ 25 ].The proportion surviving increases as birth weight increases, which means that neonates with low birth weights stayed in hospitals for a longer period of time than those with normal birth weights.…”
Section: Discussionsupporting
confidence: 83%
“…Another possible reason could be that people living in rural areas tend to be poorer than their urban counterparts' area, a factor known to have an impact on the neonatal outcome.GA is also another important determinant of neonatal mortality in our metaanalysis. Accordingly, neonates born as preterm were almost one and half times more likely to die than those term neonates [49][50][51][52][53][54][55][56][57][55], [56] , [52] , [53], [50] , [7] [51] , [49,57].RDS are an important determinant of neonatal mortality although not statistically significant in our meta-analysis. Neonates who had RDS were one times more likely to die as compared to those who did not have RD.…”
Section: Discussionmentioning
confidence: 99%